Optimizing the Utilization of the Maritime Service Industry in Supporting the National Defence Strategy at Sea - Harahap, Roqi Munthazar; Luther, Marthin; Fartianto, Gurtom (IJOSMAS, 2023)
This study aims to analyse and identify the potential for optimizing the maritime service industry in supporting the national defence strategy at sea. Oceans have become a crucial strategic asset in achieving the security and sovereignty of a country. Therefore, efforts to effectively utilize the maritime service industry are very important. This research will be conducted through a descriptive approach and quantitative analysis by collecting data from various sources, including the latest literature, related government policies, and maritime industry data. SWOT analysis will be used to evaluate the strengths, weaknesses, opportunities and challenges faced by the maritime service industry in supporting the country's defence strategy at sea. It is hoped that the results of this research will provide a more comprehensive understanding of the potentials and obstacles that exist in the utilization of the maritime service industry as part of the national defence strategy at sea. The findings from this research can be the basis for developing policies that are more effective in increasing the role of the maritime service industry in supporting maritime security and national interests